Unsur Perbuatan Melawan Hukum Dalam Praktik Peradilan Sebuah Studi Kasus - H. Chandera (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract In the process of making an agreement, all parties must pay attention to the conditions for the validity of the agreement and carry out in good faith. Any agreement that is contrary to the laws and regulations will have legal consequences